New imaging technology could predict patient response to NMD treatment.
Since not all patients respond to disease or treatment in the same manner, it is of vital importance for physicians to run tests on large cohorts. When facing rare diseases such as Duchenne muscular dystrophy (DMD), however, such cohorts just don't exist and other methods are required. Novel imaging technology developed under the BIOMAGE-NMD project aims to fill this gap.